Meaning without truth - Predelli, Stefano, 1961- (Oxford University Press, 2013)
Stefano Predelli explores the relationships between semantic notions of meaning and truth. He develops a 'Theory of Bias' in order to approach notorious semantic problems, offers a solution to Quine's 'Giorgione' puzzle and a new version of the demonstrative theory quotation, and defends a bare-boned approach to demonstratives and demonstrations.